Studi Potensi Pencemaran Lingkungan Dari Kegiatan Pertambangan Emas Rakyat Poboya Kota Palu - Ruslan Ruslan; Khairuddin Khairuddin (Hasanuddin University, 2010)
Study of environmental pollution potential of gold mining activities of Poboya society had been done. The aim is to obtain information on the amount of mercury concentrations in the river, tromol activity and the burning process of amalgam. The data was collected by survey and interview methods, while water and sediment sampling in rivers, wastewater and solid at tromol activity, and soil sampling around the burning of amalgam at different distances. The result showed that the presence of metallic mercury from mining activities both traditional mining using large discs made since the year 2007 and those that use Tromol which has been underway since August 2009 until now. The highest concentration of mercury in the river was 0.080 ppm, and the lowest was 0.005 ppm and the highest river sediment was 58.000 mg/kg, the lowest was 4.000 mg/kg. Then the concentration of mercury in waste water supreme tromol activity was 0.040 ppm, and the lowest was 0.005 ppm and the highest solid waste (tailings) was 88.2 mg /kg, the lowest was 80.8 mg/kg. Mercury levels around the burning of five sampling locations with different distances between 45.5 mg/kg to 99,90 mg/kg. Partially contained metal mercury at some point in the example has exceeded the maximum allowable concentration limit in a holistic and unsafe condition had been beyond its maximum concentration and water quality standard, sediment, wastewater and solid waste as required.Keywords : Traditional mining, Mercury.